Factors affecting hotels' adoption of mobile reservation systems: A technology-organization-environment framework. (April 2016) - Wang, Yi-Shun; Li, Hsien-Ta; Li, Ci-Rong; Zhang, Ding-Zhong
Abstract: This study explores why hotels adopt mobile reservation systems; based on a technology-organization-environment (TOE) framework, nine factors are hypothesized to explain hotels' adoption of mobile hotel reservation systems (MHRS). Logistic regression is employed to analyze data gathered from 140 hotels in Taiwan. The results indicate that compatibility, firm size, technology competence, and critical mass are significantly positively related to MHRS adoption, while complexity is significantly negatively related to MHRS adoption. By indentifying the predictors of hotels' adoption of MHRS through the TOE framework, this study provides several theoretical and practical implications related to mobile service adoption. Highlights: We explore why hotels adopt mobile hotel reservation systems. Compatibility constitutes a facilitator, while complexity is an inhibitor. Firm size constitutes a facilitator, as does technology competence. Critical mass is found to be a facilitator.